If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -22 = 6y + 2(y + 5) Reorder the terms: -22 = 6y + 2(5 + y) -22 = 6y + (5 * 2 + y * 2) -22 = 6y + (10 + 2y) Reorder the terms: -22 = 10 + 6y + 2y Combine like terms: 6y + 2y = 8y -22 = 10 + 8y Solving -22 = 10 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. -22 + -8y = 10 + 8y + -8y Combine like terms: 8y + -8y = 0 -22 + -8y = 10 + 0 -22 + -8y = 10 Add '22' to each side of the equation. -22 + 22 + -8y = 10 + 22 Combine like terms: -22 + 22 = 0 0 + -8y = 10 + 22 -8y = 10 + 22 Combine like terms: 10 + 22 = 32 -8y = 32 Divide each side by '-8'. y = -4 Simplifying y = -4
| -13x+12-11+15x=4(3x-7)-1 | | 4/7x=3/14 | | 2.99=1999+199 | | 1/2z+7=-3 | | 4x+3x-140=56 | | 7z+11-4-1+1=31 | | 2m-5/9 | | (3c-3)(4c+8)= | | 8w+6=-2(w-7) | | lx+3l=3x+6 | | 3(x+5)-2x=15 | | 6x-77+2x=43 | | -16/9=-8u | | 7x-2(1+3x)=2 | | 18+5w=3w-10 | | 5y-3/5=4/3 | | -(3v+4)=6v-3(3v+2) | | 77+4x=43 | | -2x(3x+4)+y=0 | | 0+1x=0.2(x+2) | | 3W-6+6W=-2+W | | -2/3t=6 | | 5x-x=12+6x | | 9w-2=-1w-22 | | -x-40+4x=26 | | 7v/6=-35 | | 4(x-5)+4(x-5)+3(x+6)+3(x+6)= | | 8y+9y-y-4+1y-4y=36 | | 5n-7=5(n+2)+3 | | A=pt-3p | | 1/2-3=9 | | 9(8-12w)= |